Acercamiento existencialista al drama La noche de los asesinos de José Triana. El papel de la ‘mirada’ en las relaciones intersubjetivas - Ordones, Damary (Latin American Theatre Review, 2016)
The influence of existential philosophy in the Cuban literary production that blossomed after the 1959 Revolution has been little studied by scholars so far. This is probably due to the presence of other philosophical theories, such as American Pragmatism and the positivism of Cuban philosopher Enrique José Varona, or because many professors of philosophy from the University of Havana migrated to the United States after 1959. It seems certain, however, that the initial euphoria over the new social and political environment in Cuba meant that authors were reluctant to accept existential schools of philosophy and their accompanying pessimism. Nevertheless, there are some post-revolution Cuban literary productions that display existentialist aspects. One of these is the play La noche de los asesinos by José Triana, in which it is possible to see how the gaze of the other robs us of our inherent freedom and causes us to deprive ourselves of our existence.